(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The straw-coloured fruit bats (Eidolon helvum) are the most widely distributed megachiropteran species in Africa. Studies have shown that they migrate, and are likely exposed to environmental pollutants across population. This study was designed to investigate genotoxicity via the bone marrow micronucleus assay and haematological alterations of Eidolon helvum in the tropics. Healthy straw-coloured fruit bats (Eidolon helvum; n=20) were captured from two geographical regions, Ogun and Gombe States in Nigeria and were grouped based on sex and age. Blood samples were collected for haematology and osmotic fragility, and bone marrow samples for genotoxicity studies. Results showed no significant differences in erythrocytes and leucocytes values across age and sex. The erythrocytes osmotic fragility was higher in juvenile than in adults at 0 and 0.1%NaCl, while it was higher in adult males than in adult females at 0 and 0.3% NaCl. The erythrocytes and leucocytes parameters in straw colored fruit bats were within the reference values seen in literature except the higher monocyte counts suggesting chronic inflammation. There were increased levels of micronucleated polychromatic erythrocytes and normochromatic erythrocytes in the straw-coloured fruit bats indicating genotoxicity and cytotoxicity, respectively. The present study provided baseline research data on the haematology and micronucleus profile of the straw-coloured fruit bats in Nigeria. This is perhaps the first study on haematology and micronucleus assay of in straw-colored fruit bats in the tropics